Can prognostic factors be used to direct therapy in chronic lymphocytic leukemia? - Sellner, Leopold; Dietrich, Sascha; Dreger, Peter; Glimm, Hanno; Zenz, Thorsten (Current hematologic malignancy reports, 2012)
Chronic lymphocytic leukemia (CLL) shows a heterogeneous clinical course, which can be explained in part by prognostic factors. Most patients do not need treatment at the time of first diagnosis. The identification of prognostic factors is of major interest if strategies can be devised to treat patients according to their individual risk profile or biological subgroup. Currently, in spite of a wealth of prognostic factors, individualized treatment approaches in different genetic or risk groups are the exemption in CLL. This review summarizes the most important prognostic and predictive factors in CLL, with particular emphasis on factors affecting treatment decisions in clinical trials and routine practice.
Gesehen am 04.07.2018